PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR AKIDAH AKHLAK - binti khoiriyah; nur laili; masrurotul mahmudah (Al-Mudarris: Journal Of Education, 2018)
This study was conducted for the purpose of know the application ofÂ  approach CTL in their experiences of the results of grade 5 on student Akidah Akhlak in MIMU Tulung Jaya Sukadana east Lampung . The research is research the act of class .The collection of data using technique, observation, a test, interviews and documentation .This study was conducted in 2 cycles with every cycle 2 meeting . The subject of study this is students grade 5 MIMU Tulung Jaya with the number of 23 students on Akidah Akhlak. The result of this research showing that in learning by applying approach CTL study results students increased this cycle visible on student learning I the result was completeness 65,22 % and on cycle II to achieve 86,95 %. I to cycle cycle II increased by 21,73 % .So that it can be analyzed that that the implementation of the approach CTL in learning activities can improve learning outcomes students grade 5 MIMU Tulung Jaya on the subjects Akidah Akhlak.